Nutritional quality and intake of golden botton forage (Tithonia diversifolia) in goats - Elizondo Salazar, Jorge Alberto (2021)
Introduction. Goats have adapted to variable environmental conditions and have the ability to survive in sparsely vegetated areas; however, their productive performance will be significantly affected by poor diet. Objective. To evaluate the nutritional quality of golden botton forage (Tithonia diversifolia) from the selection and consumption by goats. Materials and methods. The experiment was carried out in the “Alfredo Volio Mata” Experimental Station of the University of Costa Rica from September to November 2019. Golden botton forage was extracted from a crop with a year of established and was harvested at a regrowth age of 50 days and was fed to 16 non-lactating and non-pregnant Saanen, LaMancha and Toggenburg goats, with an average live weight of 48±5 kg. Fresh forage was offered in its entirety as harvested. Animals were placed in 2 pens of 12 m2 each and received the forage in a ratio of 20% of their live body weight as green forage, in 6 equal portions distributed throughout the day. The experimental period was 73 days, which included a 28-day period for adaptation to the new diet and to the groupmates. Results. On average, goats consumed 6580±2430 g of fresh forage per day (13.6±5.0% of their live weight) which corresponded to 700±210 g per day (1.44±0.4% of its live weight) of dry matter. No significant differences (p>0.05) were found between the concentration of nutrients in the offered and rejected forage. Crude protein concentration in forage did not exceed 17.2% and daily consumption per animal of this nutrient was on average 130±70 g. Neutral detergent fiber concentration in forage was less than 38%. Conclusion. Golden button forage harvested at 50 days of regrowth presented an adequate nutritional content and is considered as one more alternative for feeding goats.